Reproducibility and construct validity of three non-invasive instruments for assessing the trunk range of motion in patients with low back pain - Gabrielle Zoldan Ganzalez; Lucíola da Cunha Menezes Costa; Alessandra Narciso Garcia; Silvia Regina Shiwa; Cesar Ferreira Amorim; Leonardo Oliveira Pena Costa (Universidade de São Paulo, 2014)
Although there is a wide variety of methods and instruments aiming to assess the trunk range of motion, there is uncertainty regarding their construct validity and reproducibility. The objective of this study was to verify the construct validity and intra and inter-rater reproducibility of the goniometer, inclinometer and electrogoniometer in measuring the trunk range of motion in patients with history of low back pain. The measurement properties of reliability, agreement and construct validity were tested in 58 patients with low back pain using a test-retest design at baseline and after 24 to72 hours. All instruments showed good construct validity (r>0.60) as well as good levels of intra and inter-rater reliability with measurement errors ranging from 2.83 to 16.42 degrees. Among the assessed movements, the inclinometer, goniometer and electrogoniometer instruments can be considered as having good levels of construct validity and reproducibility for the assessment of trunk range of motion in patients with low back pain.